For the people : American populist movements from the Revolution to the 1850s - Formisano, Ronald P., 1939- (Caravan Book., 2008)
From the Anti-Federalists to the Know-Nothings, Formisano traces populist political movements in the U.S. chronologically from the Revolution to the Civil War, contextualizing them and demonstrating the progression of ideas and movements. Although American populist movements have typically been categorized as either progressive or reactionary, left-leaning or right-leaning, Formisano argues that most populist movements exhibit liberal and illiberal tendencies simultaneously. By considering these movements together, Formisano identifies commonalities that belie the pattern of historical polariz.